Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Aparatur Sipil Negara pada Kantor Camat Lamuru Kabupaten Bone - Yusriah Amaliah; Ahmad Rosandi Sakir (Jurnal Relasi Publik, 2023)
Transformational leadership is a leadership approach that focuses on developing and empowering subordinates, with the aim of creating significant change in the organization. This leadership style involves inspiration, motivation, and positive influence of a leader on subordinates. In the context of state administration, transformational leadership can directly impact the performance of civil servants, including civil servants in the Lamuru sub-district office of Bone Regency. Bone Regency is one of Indonesia’s regions with its own potential and challenges in development. In carrying out its duties, the Lamuru Subdistrict Office as a representative of local government at the sub-district level has a strategic role in organizing various state administration activities, coordinating development programs, and providing public services to the community. To achieve these goals, quality and effective ASN performance is essential.The research method used in this study is a Qualitative Research Method on the Effect of Transformational Leadership on the Performance of the State Civil Apparatus at the Lamuru Subdistrict Office of Bone Regency can be used to gain a deep understanding of the experiences, perceptions, and meanings associated with the phenomenon of leadership and the performance of civil servants in specific contexts.Transformational leadership has a significant influence on the performance of the state civil apparatus (ASN) at the Lamuru Subdistrict Office of Bone Regency. Through transformational leadership, a leader is able to inspire, motivate, and influence civil servants to achieve better performance and make maximum contributions in carrying out their duties. This study highlights several important findings related to the influence of transformational leadership on the performance of civil servants in the Lamuru Subdistrict Office of Bone Regency. By paying attention to the influence of this transformational leadership, the Lamuru Subdistrict Office of Bone Regency can improve the performance of civil servants, and quality public services, and strengthen public trust in the local government. Effective implementation of transformational leadership requires organizational support, leader commitment, effective communication, subordinate participation, good team building, and appreciation for achievements.